THE LEGAL PERSPECTIVE ON CONSUMER PROTECTION OF GENETICALLY ENGINEERED FOOD PRODUCTS IN INDONESIA - Rusli, Tami; A, Tandaditrya Ariefandra; Jainah, Zainab Ompu (Jurnal Pembaharuan Hukum, 2023)
The development of science and technology has triggered the use of genetic engineering. Genetic engineering is the transplantation of genes into other genes, both between genes and across genes, to produce valuable products for living creatures. Genetically engineered food products, due to the development of modern biotechnology in the field of genetic engineering technology, have given rise to new legal problems because of the possibility of posing a risk to human health. This research uses a normative juridical approach with an emphasis on secondary data. This research uses doctrinal research methods. The research specifications used are analytical descriptive. The research results show that there is no special legal protection for consumers of genetically engineered food products, because it still refers to consumer protection contained in the UUPK. It should be noted that genetic effects resulting from human genetic engineering need legal protection. Protection and intellectual property rights, where everyone, individually or collectively, must be a consumer of goods and services, so the parties need equal legal protection. Therefore, the responsibility of producers of genetically engineered food products for consumer losses must be able to fulfill the principle of justice because the economic position of producers is higher than that of consumers. By implementing the principle of absolute responsibility, the producer responsibility law will foster an attitude of caution for producers of genetically engineered food products to maintain the quality of their products.